Ownership Structure and Auditor Choice: Evidence in State-Owned Enterprises in Indonesia - Rudy Hartanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study was conducted to examine whether the ownership structure, namely large shareholders and multiple shareholders in SOE, has an influence on the selection of external auditors through the approach to ownership structure and board characteristics. This test is carried out on SOEs listed on the Indonesia Stock Exchange (IDX). The sample in this study is as many as 20 SOEs have been listed on the IDX, with a total 120 samples of SOEs from 2016 to 2021. The test results show that the ownership structure consisting of multiple large stakeholders and large stakeholders has no effect on auditors’ choice. This can happen because the ownership structure of all SOEs is still dominated by ownership from the government. In addition, independent commissioners also have no influence on auditors’ choice. An independent commissioner in a SOE is a matter that must be fulfilled based on the laws and regulations. Other findings in the form of firm size and audit committee have a positive effect on auditor choice. This shows that the larger a SOE and the more audit committees, the greater the need for a better audit than the big four auditors.